Incentive and Community Forest. (2nd December 2017) - Sarkar, Sukumar
ABSTRACT: Incentives (reward, punishment or both) matter in collective action for the provision of public goods which are community forest, fishery, irrigation. While reward increases cooperation directly, punishment serves as an indirect incentive that decrease free riding to increase contributions to public goods like community forest. The researchers find that punishment and a combination of both punishment and reward are effective in promoting cooperation by reducing conflicts. The effectiveness of incentives also depends on cost/benefit and sources of incentives. People's attitude and location of public goods are also affecting the incidence of conflicts. Researchers have also seen that combination of reward and punishment is applicable to the forest community with high group maturity and it is more institutionally effective in conflict resolution. Hence, in Joint Forest Management (JFM) the combination of reward and punishment leads to the most cooperative outcome.